Evaluating interhemispheric cortical responses to transcranial magnetic stimulation in chronic stroke: A TMS-EEG investigation. (8th April 2016) - Borich, Michael R.; Wheaton, Lewis A.; Brodie, Sonia M.; Lakhani, Bimal; Boyd, Lara A.
Highlights: Abnormal interhemispheric connectivity likely contributes to disability after stroke. TMS-evoked EEG responses used to evaluate interhemispheric motor connectivity. Increased interhemispheric motor connectivity observed after stroke during activity. Abnormal TMS-evoked interhemispheric connectivity may relate to motor impairment. Novel approach to probe network connectivity underlying stroke-related disability. Abstract: TMS-evoked cortical responses can be measured using simultaneous electroencephalography (TMS-EEG) to directly quantify cortical connectivity in the human brain. The purpose of this study was to evaluate interhemispheric cortical connectivity between the primary motor cortices (M1s) in participants with chronic stroke and controls using TMS-EEG. Ten participants with chronic stroke and four controls were tested. TMS-evoked responses were recorded at rest and during a typical TMS assessment of transcallosal inhibition (TCI). EEG recordings from peri -central gyral electrodes (C3 and C4) were evaluated using imaginary phase coherence (IPC) analyses to quantify levels of effective interhemispheric connectivity. Significantly increased TMS-evoked beta (15–30 Hz frequency range) IPC was observed in the stroke group during ipsilesional M1 stimulation compared to controls during TCI assessment but not at rest. TMS-evoked beta IPC values were associated with TMS measures of transcallosal inhibition across groups. These results suggest TMS-evoked EEG responses can index abnormal effective interhemispheric connectivity in chronic stroke.